INTERETHNIC COMMUNICATION-A FACTOR IN THE STABILITY OF CULTURAL SPACE (American Journal of Pedagogical and Educational Research, 2023)
This article cites a philosophical analysis of interethnic relations as an important factor in ensuring the stability of cultural space. Also, some specific aspects of cultural space are revealed in detail.